A small lead-cooled reactor with improved Am-burning and non-proliferation characteristics. (December 2018) - Wallenius, Janne; Bortot, Sara
Highlights: An Am transmutation rate of 25 kg/TWh is possible to achieve in a small critical lead-cooled reactor. Axial expansion of the fuel provides sufficient negative feedback. The plutonium present in the spent fuel of the reactor is less suitable for weapons production. Abstract: In this paper, a novel approach for transmutation of americium in fast reactors is presented. Using enriched uranium as fissile support, rather than plutonium, it is shown that a minor actinide burning rate of 25 kg/TWh th is possible to achieve in a passively safe, critical lead-cooled reactor. Moreover, the plutonium produced by transmutation of 241 Am features up to 38% 238 Pu, making it difficult to use for weapons production.